Analysis of Accounting Information Systems - الشريف يونس (Dirasat in Economics and Business, 1981)
Accounting is an activity that identifies, measures and communicates economic information in order to permit informed judgement and decisions by users of this information. In order to perform this activity, each business organization must have an accounting information system. A system is a collection of resources, such as people and equipment, designed to transform economic data into useful information. Accounting information systems have been developed from manual to machine and finally to electronic systems in order to satisfy expanding needs of business organizations. Also, the introduction of computers in business data processing has changed most accounting informatiön systems to become what is known as "Management Information Systems' As a result of these developments, business firms should review their accounting information systems continuously to make sure that these systems satisfy their expanding needs of information. Therefore, the need for services of Consultants in the area of accounting information systems has increased. A systems work or study usually consists of three phases: systems analysis, systems design, and systems implementation. The objective of this article has been to examine the methodology of conducting the first phase of accounting information systems work, i.e., systems analysis.